APLIKASI DATABASE TUNGGAKAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK BUMI DAN BANGUNAN KOTA METRO - Pamuji Setiawan (Jurnal TAM (Technology Acceptance Model), 2016)
The problems that exist in the report of the Job Training is "How Making an appeal letter and letters of reprimand are already computerized but at the time of writing the name, address and the amount of tax arrears frequent errors in and it happens On Collection Section Tax Office of Earth Building Metro ". Based on the information and data obtained, the results of research on database applications delinquent taxpayers on the Tax Collection Section Office Building Metro Earth, it can be a conclusion. For information and warning of a letter of appeal to the Tax Office Collection Section of Earth Building Metro still be computerized with Microsoft Excel application program so that frequent errors in the writing of the name, address and arrears as of a letter of appeal and warning letters that have been completed. To improve the effectiveness and efficiency of employees, and to avoid difficulties in the Making an appeal letter and letters of reprimand that is running now, the program proposed Writer namely visual Basic (VB) 6.0.